Cultura digitală pentru seniori: servicii IT la Filiala „M. Lomonosov” : Natalia Ciorbă - admin, admin (BIBLIOPOLIS, 2023)
The lack of digital literacy among older people is a worldwide problem. Technological progress has fundamentally changed our world. Work, education, leisure, communication and many other activities are already taking place in the digital space. It is very convenient and saves time and money. It so happened that the Library. M. V. Lomonosov is in great demand among the category of users of advanced age. Often, the older generation faces difficulties in mastering digital devices due to a large number of fundamental limitations. The author speaks about the services organized in the library: "Computerra for pensioners" and Tablet for beginners.